Marfan syndrome in a large family: response of family members to a screening programme. Issue 2 (February 1992) - Bridges, A B; Faed, M; Boxer, M; Gray, J R; Bundy, C; Murray, A
Abstract : Reaction to medical, social, and genetic implications of Marfan syndrome was evaluated by means of two questionnaires, the first after various tests before discussion of the diagnosis, the second after full discussion of the patient's diagnosis. Thirty-seven members of a family known to be at risk for Marfan syndrome attended for both questionnaires. All patients claimed to be satisfied with the way they were informed of the results of screening; 41% of patients were more worried about their health and 48% were more worried about the future after diagnosis. Apart from 50% of the smokers reducing or stopping their intake of cigarettes there were only very minor changes in lifestyle over the first month despite the increased level of expressed anxiety. If a definitive screening test was available, 96% of patients claimed they would have chosen it, 45% felt it would have an influence on their future plans, and 78% would choose to use a method of prenatal diagnosis for Marfan syndrome if it were available.